2020
DOI: 10.21037/tcr-20-66
|View full text |Cite
|
Sign up to set email alerts
|

Polyphyllin I suppresses proliferation and promotes apoptosis of gastric cancer cell by inhibiting stat3 phosphorylation

Abstract: Background: Polyphyllin I, a bioactive phytochemical extracted from Rhizoma Paridis, has been reported to exhibit anticancer activity. However, little is known about the potential of Polyphyllin I in induction of gastric cancer (GC) cell apoptosis and its underlying mechanisms. Methods: Dual-luciferase reporter assay was performed to test the bioactivity of Polyphyllin I on inhibiting JAK2/STAT3 signaling pathway. The anti-proliferation activity of Polyphyllin I was tested using cell clone formation assay. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Previous reports showed that PPI inhibited the tumor growth via several mechanisms ( Dong et al, 2018 ; Zhang et al, 2018 ; Han et al, 2020 ). In this study, we first confirmed that PPI indeed suppressed both AGS and MKN-45 cancer cell growth in vitro in a dose-dependent manner based on MTT assays ( Figure 2A, B ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports showed that PPI inhibited the tumor growth via several mechanisms ( Dong et al, 2018 ; Zhang et al, 2018 ; Han et al, 2020 ). In this study, we first confirmed that PPI indeed suppressed both AGS and MKN-45 cancer cell growth in vitro in a dose-dependent manner based on MTT assays ( Figure 2A, B ).…”
Section: Resultsmentioning
confidence: 99%
“…The transcriptional and signal pathways initiated by PPI may include STAT3, AMPK, FOXO3 and PI3K/Akt, etc. ( Han et al, 2015 ; Li et al, 2016 ; Lou et al, 2017 ; Liu et al, 2018 ; Han et al, 2020 ; Li et al, 2020 ; Lai et al, 2021 ). However, there has been no any report on a potential impact of PPI on cancer cell ferroptosis.…”
Section: Introductionmentioning
confidence: 99%
“…STAT3 has been proposed as a pathogenic factor and therapeutic target of CRC [ 20 ]. PPI, another important active component extracted from Rhizoma Paridis , has been shown to inhibit STAT3 activation in gastric cancer cells [ 12 ]. In this study, we found that PPII also suppressed the phosphorylation/activation of STAT3 in human CRC cells and the HCT116 xenografts.…”
Section: Discussionmentioning
confidence: 99%
“…Steroid saponins, such as polyphyllin I (PPI), II (PPII), VI (PPVI), and VII (PPVII), are active ingredients identified in Rhizoma Paridis . Among these polyphyllins, PPI has a significant therapeutic effect on hepatocellular carcinoma, CRC, melanoma, prostate cancer, and gastric cancer by inducing cell cycle arrest, apoptosis, and autophagy, as well as by inhibiting the activation of STAT3 and the PI3K/AKT/mTOR signaling pathways [ 11 , 12 , 13 , 14 ]. PPVI has been demonstrated to provoke apoptosis and autophagy in human osteosarcoma cells [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, application of inhibitors targeting the Janus kinase 2/signal transducer and activator of transcription 3 (JAK/STAT3) pathway (e.g., AG490) may have a strong effect in anti-gastric cancer therapy (Bogani et al, 2013). Studies have confirmed that polyphyllin I mainly inhibits the phosphorylation of STAT3 in a way that inhibits the expression of apoptosis-related protein, such as BCL2, and induces apoptosis of gastric cancer cells (Han et al, 2020). Another experimental study confirmed that polyphyllin I promotes the transformation of mesenchymal cells to epithelial cells, thereby partially inhibiting the migration and invasion of gastric cancer cells.…”
Section: Other Antitumor Activities Of Polyphyllin Imentioning
confidence: 99%